(untitled) (International Journal of Artificial Intelligence, Computer Science, Management and Technology, 2025)
Blockchain and smart contracts are reshaping the foundations of trust and transparency in collaborative environments by offering decentralized, immutable, and verifiable mechanisms for data exchange and transaction automation. This paper investigates how these technologies facilitate transparent collaboration across diverse sectors such as supply chain, healthcare, finance, and Internet of Things (IoT) networks. Employing both doctrinal and non-doctrinal research methods, the study analyzes legal frameworks—like U.S. state-level recognition of smart contracts—and empirical adoption trends based on recent data from 2024–2025. The findings highlight blockchain’s potential to reduce reliance on centralized authorities, enhance data integrity, and automate contract execution with minimal human intervention. However, challenges remain in terms of legal enforceability, lack of regulatory uniformity, complexity of smart contract interdependence, and the risks posed by immutability in evolving business contexts. Real-world implementations like TradeLens, Chainlink, and Canton Network are critically examined to underscore both opportunities and systemic challenges. Tables and graphical visualizations further enrich the data analysis, revealing adoption patterns and market trajectories. The paper concludes that hybrid governance structures, privacy-preserving smart contract architectures, and legally harmonized standards are vital for unlocking blockchain’s full potential in enabling transparent and trustworthy collaboration.